Sistema de base de datos de especies de vegetales CIRNA-UNAP - Aranda Cárdenas, Katherin (2021)
The purpose of this work is to implement a system that records and stores information on plant species for the Natural Resources Research Center (CIRNA), this research was of an applicative type with a descriptive level, whose design is non-experimental of a transactional type, The study sample is made up of CIRNA-UNAP workers and researchers, the information collection method is the survey method using the questionnaire technique, in this context it was possible to contrast the hypothesis of the proposed research: “The Implementation of an information system will improve the registration of information on plant species for the Natural Resources Research Center.